Pengaruh Product Knowledge, Green Product Persepsi Harga terhadap Minat Beli Ulang Tupperware di Bandung Raya - Yulianti, Sani; Adialita, Tania (J-MAS (Jurnal Manajemen dan Sains), 2024)
The use of single-use plastic bags and packaging is still widely used by the public for the reason that it is more practical and cheaper, this is due to the lack of public knowledge about the dangers of using plastic and environmentally friendly products, apart from the opinion that bringing your own food container when snacking is considered less practical and the price is considered more expensive than single-use plastic. This research aims to analyze the influence of product knowledge, green products, and price perceptions on interest in repurchasing Tupperware in Greater Bandung. The population in this research is Tupperware buyers and users over 18 years of age and domiciled in Greater Bandung. This research used a convenience sampling technique involving 150 respondents. The data used is primary data obtained from survey results through distributing questionnaires online using cross-sectional data collection techniques. This research uses analytical techniques of validity testing and reliability testing to test instruments, classical assumption testing, and hypothesis testing using SPSS version 24. The results of this research are that product knowledge significantly influences interest in repurchasing Tupperware products, green products influence repurchase interest , price perception does not influence interest in repurchasing Tupperware. The research results simultaneously show that product knowledge, green products, and price perceptions influence interest in repurchasing Tupperware in Greater Bandung..